2014
DOI: 10.3390/rs6065852
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Surface Urban Heat Islands over Three Megacities in East Asia Using Land Surface Temperature Data Retrieved from COMS

Abstract: Surface urban heat island (SUHI) impacts control the exchange of sensible heat and latent heat between land and atmosphere and can worsen extreme climate events, such as heat waves. This study assessed SUHIs over three megacities (Seoul, Tokyo, Beijing) in East Asia using one-year (April 2011-March 2012) land surface temperature (LST) data retrieved from the Communication, Ocean and Meteorological Satellite (COMS). The spatio-temporal variations of SUHI and the relationship between SUHI and vegetation activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 29 publications
3
32
0
1
Order By: Relevance
“…Feng et al [] found that urban growth has little impact on surface UHIs. Choi et al [] showed that surface UHIs over Beijing had a strong negative correlation with vegetation coverage during daytime, but such a relation was not observed during nighttime. Kuang et al [] studied the relationship between surface UHIs and vegetation coverage over Beijing and argued that the city should upgrade the traditional low‐rise residential areas to high‐rise residential areas to reduce UHI intensity.…”
Section: Introductionmentioning
confidence: 99%
“…Feng et al [] found that urban growth has little impact on surface UHIs. Choi et al [] showed that surface UHIs over Beijing had a strong negative correlation with vegetation coverage during daytime, but such a relation was not observed during nighttime. Kuang et al [] studied the relationship between surface UHIs and vegetation coverage over Beijing and argued that the city should upgrade the traditional low‐rise residential areas to high‐rise residential areas to reduce UHI intensity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, for Tokyo, a significant correlation was observed for spring and autumn UHI intensity. As developed megacities of East Asia, several previous studies identified the UHI phenomenon in Seoul and Tokyo [14,43,44]. Specifically, in Tokyo, widespread urban warming, known as the extended heat island, appeared in summer because of enhanced surface heating over a large urban area and reduced sea-breeze penetration caused by the increased surface convergence ( Table 2) [45].…”
Section: Correlation Analysismentioning
confidence: 99%
“…(Moran and Jackson, 1991;Kustas and Norman, 1996;Benali et al, 2012;Choi et al, 2014). 다양한 응용분야에서 지표면온도의 중 요성이 부각됨에 따라 시·공간적으로 높은 해상도로 관측된 정량적인 지표면온도의 필요성이 증대되고 있 다 (Wan and Dozier, 1996;Li et al, 2013).…”
Section: 서 론unclassified